A Literature Survey of the Fracking Economic and Environmental Implications in the United States. (2015) - Mehany, Mohammed S. Hashem M.; Guggemos, Angela
Abstract: This paper presents an intensive survey of literature focused on the different aspects of fracking as related to the environment, economy, energy security and sustainability and establishes an understanding of the economic benefits and negative impacts of fracking on the environmental sustainability. The paper is also suggesting the use of all of those implications in a more comprehensive framework that can identify the real cost and benefit in fracking such as the Life Cycle Costing which can use all these implications along with others that occur across all the phases of the fracking process to come up with the real value and worth of the fracking process.